Contabilidade de Organização da Sociedade Civil de Interesse Público - OSCIP: ênfase no registro contábil das despesas, receitas e apuração de resultados - Ribeiro, Sandra Mara (2012)
The OSCIP, with activities aimed at developing social improvements in the communities, need more and more tools that make these Oganizations reliable enough both for the society and for the government. Accounting, as a social science, is able to provide this instrument, that brings transparency for the third sector institutions. Relying on this credibility, these organizations may atract more investors , and as a result, achieve their objectives. This paper considers the need of specific technical knowledge, regarding the procedures to be adopted in the execution of the accounting data registering performed by an OSCIP (Organização de Sociedade Civil de Interesse Público). Since the approval of the law 11.638/07 up to the CPC s published that make reference to the sector. Along this paper, some legal tax characteristics will be cited. These characteristics enables the instituition to take advantage of tax exemptions/immunity no matter they are Federal, State or municipal taxes. Since its beginning until today, much has to be discussed regarding the performance of accounting as an indispensable tool, both for regulation organs as well as for funders. We ll assess a brief survey about the analysis theories applicable to the third sector institutions taking into account the registration of expenses and income, as well as the generated impacts over the results